(untitled) (Experimental biology, 2016)
This article presents the results of studies on the floristic composition of plant communities with Echinops albicaulis Kar. & Kir. in the area of the pass Malaysary. The floristic composition of the community was represented Echinops 25-30 species of vascular plants. The most characteristic of these associations with the participation of Echinops albicaulis: calligonum-different-herb-grass, сalligonum- different-herb-grass-echinops, аrtemisia - echinops and аrtemisia. The floristic composition of plant communities with Echinops albicaulis characterized by agricultural significance. In economic value allocated 10 types of medicines, 14 kinds of food, 3 kinds of food, 4 kinds of technical, 9 species of ornamental, 3 kinds of honey, 6 and 4 species of poisonous species of rare endangered plants. Аgricultural significance allocated 10 types of medicines, 14 kinds of food, 3 kinds of food, 4 kinds of technical, 9 species of ornamental, 3 kinds of honey, 6 and 4 species of poisonous species of rare endangered plants. The floristic composition of Echinops community was presented 25-30 species of vascular plants.